IDENTIFIKASI HAMBATAN DALAM PELAKSANAAN PROGRAM USAHA KESEHATAN SEKOLAH (UKS) DI SDN INPRES LIWUTUNG 2 KECAMATAN PASAN - Estelina J Posumah; Prycilia P (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2025)
School Health Business is one way to foster and develop healthy lifestyles in schools. This type of research is qualitative using observational. The research was conducted in March-April at SDN Inpres Liwutung 2, Pasan District. The research informants were school principals, school health business advisors (UKS), community health center officers. Data analysis used by means of in-depth interviews, was carried out inductively and continued continuously until completion, so that the data was complete. Analysis consists of three activity streams that occur simultaneously, namely: data reduction, data presentation and data drawing conclusions/verification. The results of this research show that UKS funding comes from BOS funds which are regulated for school activities and needs, one of which is for UKS, but these funds are not sufficient for UKS room needs. For training, Puskesmas officers have not yet facilitated training for UKS supervisors and UKS cadres, because the puskesmas has not received training and orders from the health service to carry out supervisor training. UKS and UKS Cadres. The school's UKS infrastructure is not yet good, the UKS is not spacious enough and there are limited beds, examination tables, folding stretchers, blankets, scales, student health records, thermometers and blood pressure meters.